The Effect of Delegation of Authority Policy Implementation and Employee Performance on PATEN Effectiveness in Tarogong Kaler District, Garut - Diki Kurnia; Gugun Geusan Akbar; Widaningsih (Politeia : Journal of Public Administration and Political Science and International Relations, 2026)
This study examines the implementation of the District Integrated Administrative Services (PATEN) in the Tarogong Kaler District Office, Garut Regency. Despite the policy's goal to bring services closer to the community, empirical data shows suboptimal effectiveness, indicated by a 78.4% service completion rate, delays, and a decline in the SAKIP predicate from BB to B. This paper addresses the research question of how the implementation of the Garut Regent's Regulation on the Delegation of Authority and employee performance influence PATEN effectiveness. The novelty lies in combining policy implementation parameters with employee performance metrics within the specific bureaucratic context of Tarogong Kaler. A quantitative descriptive-associative research design was employed. The population and sample consisted of 47 respondents (21 sub-district employees and 26 village apparatuses) selected through a saturation sampling (census) technique. Data were collected via Likert-scale questionnaires, interviews, and observation, then analyzed using multiple linear regression with SPSS version 23. The empirical findings revealed that the variables are categorized as 'good'. The hypothesis testing demonstrated that the implementation of the delegation of authority policy and employee performance jointly exert a positive and sufficiently strong effect on PATEN effectiveness. Enhancing policy implementation and employee performance significantly increases PATEN effectiveness. However, field findings indicate that available budget support, employee work experience, and information regarding service times and costs are still suboptimal and require immediate management attention.